Drug Utilization and Potential Drug-Drug Interactions within an Intensive Care Unit at a University Tertiary Care Hospital in Egypt - Dima F. Obeid; Adel H. Karara (MDPI AG, 2022)
There are few reports on drug utilization and drug-drug interactions in Intensive Care Units (ICUs) in Egypt. A total of 94 patients participated in this retrospective observational study. Patient's medical records were used to collect demographics, medical history, admission and discharge dates and medications used. The mean ± SD of the Glasgow Coma Scale (GCS) scores was 9.9 ± 4.4 and the median length of stay was 7 days (range 1-47 days). The total number of prescribed medications ranged from 4-29 with a mean ± SD of 14.1 ± 5.5 medications per patient. The top three most prescribed categories belonged to (1) anti-infective agents (23.9%); (2) electrolyte, caloric and water balance agents (14.6%); and (3) blood formation, coagulation and thrombosis (11.3%). The proton pump inhibitor, esomeprazole, was the most frequently prescribed medication accounting for 6.5% of total prescriptions, followed by clindamycin and magnesium sulfate each accounting for 3.5% of total prescriptions. The potential Drug-Drug Interactions (pDDIs) showed a total of 968 pDDIs with a mean ± SD (range) of 10.2 ± 9.4 (0-43) pDDIs per patient: severe (contraindicated) (3), major (178), moderate (618) and minor (169). Overall, the drug utilization patterns in this study were consistent with ICU drug utilization from other countries in the region. The implementation of clinical decision support systems and the involvement of clinical pharmacists may help improve medication safety.